2017
DOI: 10.2147/ijwh.s139226
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled clinical trial of second uterine curettage versus usual care to determine the effect of re-curettage on patients’ need for chemotherapy among women with low risk, nonmetastatic gestational trophoblastic neoplasm in Urmia, Iran

Abstract: ObjectiveThe objective of this study was to determine if second curettage was associated with a decreased need for the number of chemotherapy treatments compared to usual care.MethodsA pilot randomized controlled clinical trial was designed at Motahhari Referral Hospital in 2014. Fifty-two patients with low risk, nonmetastatic gestational trophoblastic neoplasm were assigned randomly to two arms. The interventional arm included a repeat uterine curettage, and the control group received standard care (chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Its level was significantly higher in patients requiring chemotherapy. These findings were consistent with the results of study conducted by Ayatollahi et al (Ayatollahi et al, 2017), while, the study of Osbrone et al did not show the predictive value of β-hCG in response to curettage therapy (R. J. Osborne et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Its level was significantly higher in patients requiring chemotherapy. These findings were consistent with the results of study conducted by Ayatollahi et al (Ayatollahi et al, 2017), while, the study of Osbrone et al did not show the predictive value of β-hCG in response to curettage therapy (R. J. Osborne et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Osborne et al, 2016). In addition, in another study, Ayatollahi et al showed that 50% of patients were treated with re-curettage without the need for chemotherapy (Ayatollahi, Yekta, & Afsari, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The study characteristics are presented in Table 1. Two studies 18,19 were RCTs and the other three studies [20][21][22] were retrospective studies. For study location, one study 20 was performed in Egypt, two studies 21,22 were performed in European countries (Netherlands and UK) and two studies 18,19 was performed in Iran, respectively.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…20,22 It is worth mentioning that two studies were excluded in the procedure of full text review because one study 3 had no control group of conventional chemotherapy and the other study 28 administered one-cycle methotrexate for the second curettage group. Additionally, two of the included studies were authored by Ayatollahi et al 18,19 Concerns may be raised that these two studies shared the same data set as one 19 was an abstract presented at a meeting and the other 18 was a manuscript published in a journal. However, it is worth appreciating that both manuscripts had their respective study period, number of participants and method; therefore, we do not consider their data set to be identical.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…First, the authors incorporated two reports from the same study into the meta-analysis, 2,3 thereby raising concerns about the potential overestimation of the results. Although the authors contended that the study periods and participant numbers differed between the reports, both actually included the same cohort of participants.…”
Section: O R R E S P O N D E N C E Letter To the Editor: Second Curet...mentioning
confidence: 99%